Assembling animals: trees, genomes, cells, and contrast to plants - Paps, Jordi; Rossi, Maria Eleonora; Bowles, Alexander M. C.; Álvarez-Presas, Marta (Frontiers in Ecology and Evolution, 2023)
The Animal Kingdom is an astonishingly diverse group. Together with plants and fungi is one of the three major lineages of multicellular eukaryotes. Due to anthropocentrism and/or genuine scientific interest, their origin and diversification are pivotal to modern evolutionary biology. In the last few decades, dramatic technological advances in molecular biology and computational power have generated new phylogenetic proposals, as well as new tools to compare genomes or study cell type evolution. These new approaches complement the insights from fields such as comparative morphology, evodevo, or palaeontology, which all together provide an integrative view of animal evolution, including major evolutionary transitions such as the origin of animals or the emergence of animals with bilateral symmetry. In this paper, we review recent developments in animal phylogenetics, comparative genomics, and cell type evolution related to these two transitions, and we compare animals to another major lineage of multicellular eukaryotes, plants.